Is the Filipino Diaspora a Diaspora? - Aguilar, Filomeno V, Jr (Archīum Ateneo, 2015)
Despite the widespread popularity of the discourse on diasporas since the 1980s, the recognition of a Filipino diaspora in the wider Anglophone scholarly world did not occur until the mid 2000s. A major factor for this recognition was the considerable number of scholarly works on Filipino Americans produced largely by Filipino American scholars who used diaspora as theoretical frame starting in the late 1990s. Grappling with the realities of the global migrations of Filipinos, the Philippine state and Filipinos in the Philippines and in other parts of the world also began to deploy the diaspora discourse. This article analyzes the ways in which the discursive fields in the US and in the Philippines have converged or diverged. Although diaspora can be a problematic concept, the author examines methodological issues that focus not so much on identities but on the imagined and constructed collectivity within which the putative diasporan identity of Filipinos is embedded. Without reducing diaspora to a reifying checklist, the author explores the Filipino diaspora discourse along these five dimensions: (a) population dispersal from an original homeland, real or imagined; (b) a process of diasporization; (c) ongoing relationship with the homeland, nurtured by collective memory or mythology; (d) idealization of return to the homeland; and (e) self-awareness or collective consciousness that is intergenerational and interrelated to coethnics and compatriots within the diaspora.